Primary renal myxoid liposarcoma with pancreatic invasion on 18F-FDG PET/CT: first case report and literature review - Huang, Wenpeng; Chao, Fangfang; Zhang, Yongbai; Li, Liming; Gao, Yuan; Qiu, Yongkang; Gao, Jianbo; Kang, Lei (Frontiers in Medicine, 2023)
Background Myxoid liposarcoma (MLS) is a rare malignant soft tissue sarcoma that predominantly manifests in the deep soft tissues of the extremities, particularly within the musculature of the thigh. Unlike other types of liposarcoma, MLS demonstrates a propensity for metastasis to atypical sites, including the lung parenchyma, soft tissues, retroperitoneum, mediastinum, breast, liver, thymus, lymph nodes, and bones. The definitive diagnosis primarily relies on histology with HE staining. Imaging modalities such as ultrasound, CT, MRI, and 18F-FDG PET/CT scans serve as valuable tools for tumor identification. Case report A 57-year-old man presented with symptoms of abdominal distention and vomiting 1 month ago. Contrast-enhancement CT revealed a heterogeneous hypodense mass in the upper-middle part of the left kidney, displaying irregular morphology and protrusion towards the exterior of the kidney, with abundant blood supply and had a maximum dimension of approximately 10.7 cm × 9.0 cm. Additionally, a rounded soft tissue density was identified in the pancreatic body. Multiplanar reconstruction demonstrated a connection between the pancreatic lesion and the kidney mass. 18F-FDG PET/CT was conducted for staging, revealing significant growth of the lesion in the upper-middle part of the left kidney, extending beyond the kidney and infiltrating the pancreatic body. The lesion demonstrated remarkably high 18F-FDG uptake (SUVmax = 10.2, MTV = 136.13 cm3, TLG = 484.62). The postoperative pathological examination confirmed the diagnosis of MLS. On the 10th day post-surgery, the patient presented with tumor recurrence and underwent another surgical resection. Unfortunately, during the operation, the patient experienced a sudden cardiac arrest and died. Conclusion Renal MLS with invasion into the pancreas is very rare in clinical practice. Due to the limited research on the utilization of 18F-FDG PET/CT in this particular context, given the rarity and low incidence of MLS, its role remains largely unexplored. As PET/CT imaging becomes increasingly prevalent, thorough imaging of disease sites becomes indispensable for the development of treatment protocols and the monitoring of treatment response.